Renal hemodynamics in patients with chronic diffuse liver diseases - B. B. Fishman; V. Ye. Kulikov; K. Yu. Vanin; M. D. Kashayeva; G. N. Andreyev (Бюллетень сибирской медицины)
Statistically confident (р < 0,05) change of blood flow parameters in segmentary and parenchymal arteries in the form of increase of resistance and pulsativity indices has been found that in patients with high-activity chronic hepatite with hyperbilirubinemia. The highest increase of the resistance and pulsativity indices of 0,88 ± 0,05 and 1,24 ± 0,07, respectively, was observed only in segmentary arteries. No statistically confident (р > 0,05) changes were found in maximal and minimal linear parameters of blood flow in these arteries.